Genomic sequence correction by single-stranded DNA oligonucleotides: role of DNA synthesis and chemical modifications of the oligonucleotide ends. - Olsen, P; Randøl, M; Luna, L; Brown, T; Krauss, S (2005)
BACKGROUND: Single-stranded oligonucleotides (ssODN) can induce site-specific genetic alterations in selected mammalian cells, but the involved mechanisms are not known. METHODS: We corroborate the potential of genomic sequence correction by ssODN using chromosomally integrated mutated enhanced green fluorescent protein (mEGFP) reporter genes in CHO cell lines. The role of integration site was studied in a panel of cell clones with randomly integrated reporters and in cell lines with site-specific single copy integration of the mEGFP reporter in opposite orientations. Involvement of end modification was examined on ssODN with unprotected or phosphorothioate (PS) protected ends. Also ssODN containing octyl or hexaethylene glycol (HEG) end blocking groups were tested. The significance of DNA synthesis was investigated by cell cycle analysis and by the DNA polymerases alpha, delta and epsilon inhibitor aphidicolin. RESULTS: Correction rates of up to 5% were observed upon a single transfection of ssODN. Independent of the mEGFP chromosomal integration site and of its orientation towards the replication fork, antisense ssODN were more effective than sense ssODN. When ssODN ends were blocked by either octyl or HEG groups, correction rates were reduced. Finally, we demonstrate a dependence of the process on DNA synthesis. CONCLUSIONS: We show that, on a chromosomal level, the orientation of the replication fork towards the targeted locus is not central in the strand bias of ssODN-based targeted sequence correction. We demonstrate the importance of accessible ssODN ends for sequence alteration. Finally, we provide evidence for the involvement of DNA synthesis in the process.